(untitled) (Research, Society and Development, 2020)
Education is a social right and a duty of the State, and should be mandatory and free of charge throughout Basic Education (EB). In order to enforce this right, the State established the goal to guarantee the progressive universalization of access to education, however, school dropout is still one of the major bottlenecks of education in Brazil. Given this context, this article sought to demonstrate the number of enrollments and the dropout rate in high school in the State of Amapá, between 2015 and 2017, based on searches performed in the INEP database, as well as bibliographic and documentary research. These data present the sum of students enrolled in High School (EM), Integrated Technical High School (EMTI) and Included Students; and also, they show the percentage of students who left school during the period studied. The analyzed information expresses a year-on-year reduction in the enrollment rate and in the percentage of school dropouts. This behavior can be explained by the fact that the public school has the highest dropout rates and one of the highest failure rates. However, these data are conflicting, as they do not evaluate the existence of school dropout and failure due to intra and extra-school factors, percentages that interfere in the number of graduates from one grade to another in high school.